Algebra trigonometry /John W. Coburn - University of Tennessee at Martin (MCGraw - Hill, 2010)
Selected chapter from algebra trigonometry; Three components contribute to a theme sustained throughout the Coburn Series: that of laying a firm foundation, building a solid framework, and providing strong connections. Not only does Coburn present a sound problem-solving process to teach students to recognize a problem, organize a procedure, and formulate a solution, the text encourages students to see beyond procedures in an effort to gain a greater understanding of the big ideas behind mathematical concepts.